2023
DOI: 10.3390/molecules28155757
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Nanoparticles Induced Hepatotoxicity in Mice via Lipid-Metabolism-Dysfunction-Regulated Inflammatory Injury

Shuang Zhou,
Hua Li,
Hui Wang
et al.

Abstract: Nickel nanoparticles (NiNPs) have wide applications in industry and biomedicine due to their unique characteristics. The liver is the major organ responsible for nutrient metabolism, exogenous substance detoxification and biotransformation of medicines containing nanoparticles. Hence, it is urgent to further understand the principles and potential mechanisms of hepatic effects on NiNPs administration. In this study, we explored the liver impacts in male C57/BL6 mice through intraperitoneal injection with NiNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The key role played by lipids in tissue physiology and cell signaling has been demonstrated in several studies [ 46 ], which have shown that abnormal changes in lipid metabolism can lead to cellular dysfunction and necrosis, resulting in cell death. Disorders of lipid metabolism are a key factor contributing to hepatotoxic injury [ 47 , 48 ]. Glycerophospholipid is an amphiphilic molecule that is directly involved in cellular physiological functions and helps transport triacylglycerol.…”
Section: Discussionmentioning
confidence: 99%
“…The key role played by lipids in tissue physiology and cell signaling has been demonstrated in several studies [ 46 ], which have shown that abnormal changes in lipid metabolism can lead to cellular dysfunction and necrosis, resulting in cell death. Disorders of lipid metabolism are a key factor contributing to hepatotoxic injury [ 47 , 48 ]. Glycerophospholipid is an amphiphilic molecule that is directly involved in cellular physiological functions and helps transport triacylglycerol.…”
Section: Discussionmentioning
confidence: 99%